Total Productive Maintenance (TPM) Practices And Manufacturing Performance: The Moderating Effect Of Types Of Production Processes - Lazim, Halim Mad (2010)

(untitled)
The importance of maintenance has become the main focus in the manufacturing environment. New technologies and advancements in the manufacturing industry have driven many companies to implement reliable maintenance program in order to avoid stoppages and disruptions of equipment from occurring in their daily operations. Total productive maintenance (TPM), a resource-emphasized approach moves the paradigm of maintenance by putting emphasis on total employee involvement in the maintenance activities.